Using process enriched rice straw in Nepal - International Livestock Research Institute (International Livestock Research Institute, 2023)
Shreenagar, an agribusiness company in Nepal, has commercialised the production of processed enriched rice straw, a technology that was developed by ILRI, to help farmers improve the productivity of their dairy animals in the country. This product is one of the outcomes of a study on integrated nutrition package and holistic fertility management in dairy buffalo in Nepal.